A Review on various techniques of hiding Association rules in Privacy Preservation Data Mining (International Journal of Engineering and Computer Science, 2015)
Data mining is the useful technology to extract information or knowledge from large database. However, misuse of this technology may lead to the disclosure of sensitive information. Privacy preserving data mining (PPDM) is new research direction for disclosure of sensitive knowledge. There are many techniques used in PPDM to hide association rules and generated by association rule generation algorithms. Association rule hiding is the method of modifying original database to make the sensitive rules disappear. The Security and Privacy of the data are main challenging issues. The owner of the data has some private information like association rule contained old database. However the integrity of mining results can affects gravely in case of unreliable administration supplier.